MicroRNA in Metabolic Re-Programming and Their Role in Tumorigenesis - Tomasetti, Marco; Amati, Monica; Santarelli, Lory; Neuzil, Jiri (International journal of molecular sciences, 2016)
The process of metabolic re-programing is linked to the activation of oncogenes and/or suppression of tumour suppressor genes, which are regulated by microRNAs (miRNAs). The interplay between oncogenic transformation-driven metabolic re-programming and modulation of aberrant miRNAs further established their critical role in the initiation, promotion and progression of cancer by creating a tumorigenesis-prone microenvironment, thus orchestrating processes of evasion to apoptosis, angiogenesis and invasion/migration, as well metastasis. Given the involvement of miRNAs in tumour development and their global deregulation, they may be perceived as biomarkers in cancer of therapeutic relevance.
Keywords: miRNA regulating signaling pathways; regulace genové exprese u nádorů; Humans; MicroRNAs; Biomarkers, Tumor; Carcinogenesis; tumorigenesis; lidé; Metabolic Networks and Pathways; miRNAs; metabolic reprogramming; nádorové biomarkery; karcinogeneze; Tumor Microenvironment; nádorové mikroprostředí; onkogenní proteiny; metabolické sítě a dráhy; mikro RNA; Gene Expression Regulation, Neoplastic; miR-126 and cancer-stroma environment; Oncogene Proteins